Early-life stress links 5-hydroxymethylcytosine to anxiety-related behaviors - Ligia A. Papale; Andy Madrid; Sisi Li; Reid S. Alisch (Epigenetics, 2017)
Environmental stress contributes to the development of psychiatric disorders, including posttraumatic stress disorder and anxiety. While even acute stress alters gene expression, the molecular mechanisms underlying these changes remain largely unknown. 5-hydroxymethylcytosine (5hmC) is a novel environmentally sensitive DNA modification that is highly enriched in the brain and is associated with active transcription of neuronal genes. Here we examined behavioral and molecular alterations in adult mice that experienced an early-life stress before weaning (postnatal day 12 to 18) and found anxiety-like behaviors in adult female mice that were accompanied by correlated disruptions of hypothalamic 5hmC and gene expression in 118 genes, revealing potentially functional 5hmC (i.e., gene regulation). These genes are known and potentially novel stress-related targets, including Nr3c2, Nrxn1, Nfia, and Clip1, that have a significant enrichment for neuronal ontological functions, such as neuronal development and differentiation. Sequence motif predictions indicated that 5hmC may regulate gene expression by mediating transcription factor binding and alternative splicing of many of these transcripts. Together, these findings represent a critical step toward understanding the effects of early environment on the neuromolecular mechanisms that underlie the risk to develop anxiety disorders.